2019
DOI: 10.1039/c9ra00275h
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oxidation on the electronic properties of penta-graphene: first-principles calculation

Abstract: Herein, using first-principles calculations, we systematically studied the effect of oxidation on the structural and electronic properties of penta-graphene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…The dissociated oxygen atoms bind with the sp 2 -C atom to form a carboxide group or epoxide group, for example, O 2 /p-Gra-D1 and O 2 /p-Gra-D2 isomers with adsorption energies of À2.28 eV and À1.82 eV, respectively. Configuration with molecular adsorption proposed by Li et al 29 is not energetically competitive with the dissociation adsorption configuration, which one can see from Fig. S1(e…”
Section: But Nitrogenmentioning
confidence: 76%
See 2 more Smart Citations
“…The dissociated oxygen atoms bind with the sp 2 -C atom to form a carboxide group or epoxide group, for example, O 2 /p-Gra-D1 and O 2 /p-Gra-D2 isomers with adsorption energies of À2.28 eV and À1.82 eV, respectively. Configuration with molecular adsorption proposed by Li et al 29 is not energetically competitive with the dissociation adsorption configuration, which one can see from Fig. S1(e…”
Section: But Nitrogenmentioning
confidence: 76%
“…Recently, Li et al 29 investigated the structures and electronic properties of oxygen molecules adsorbed on penta-graphene and found that oxygen atoms prefer to adsorb at the center of CQC bonds as one can see from Fig. S1(d) (ESI †).…”
Section: But Nitrogenmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well known that the PG bandgap increases with an increase in oxygen doping concentration 30 32 . Such a trend is attributed to the up-shift of the conduction band minimum during the oxidation process 30 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the PG bandgap increases with an increase in oxygen doping concentration 30 32 . Such a trend is attributed to the up-shift of the conduction band minimum during the oxidation process 30 . Since oxidized PG exhibits a large bandgap, it can be considered a good alternative for the conception of new dielectric layers in electronic devices 31 .…”
Section: Introductionmentioning
confidence: 99%